Conflict and Violence against Women and Girls: Gender-based Violence and the Boko Haram in Nigeria - Yang, Mok Shen (Global and Policy Journal of International Relations, 2015)
ABSTRACTIn October 2000, the United Nations Security Council passed Resolution 1325 in which sexual violence was framed as a legitimate international peace and security issue. It brings to light the gender-dimension associated with problems faced by women and girls in time of armed conflict, especially with regards to the use of rape as a weapon of war. As the nature of war and armed conflict over the last two decades has shifted from predominantly inter-state to intra-state, this paper aims to provide another perspective to understanding violence against women in armed conflict at a domestic rather than international level. This paper focuses on the case of Boko Haram’s violence against women and girls in Nigeria, which was especially underscored by its kidnapping of the Chibok schoolgirls in 2014 that drew widespread outrage both locally and internationally. It explores how economic deprivation, institutional failures and culturally-institutionalised norms of Nigerian society goes hand-in-hand with Boko Haram’s anti-Western and anti-Christian ideology, alongside its changing operation tactics, in perpetuating violence against women and girls.Keywords: Sexual Violence, Armed Conflict, Boko Haram, Nigeria, Chibok Schoolgirls' KidnappingDOI:https://doi.org/10.33005/jgp.v3i02.1934